PENGARUH DEWAN KOMISARIS INDEPENDEN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Henryanto Abaharis (JURNAL PUNDI, 2021)
ABSTRACT This study aims to find out influence of board of commissioner, and institisonal ownership to value of the company on manufacture companies. This study objects is manufacturing company which listed in Indonesia Stock Exchange and the observation period from 2014 to 2018, the sampling technique used is purpisive sampling. This study used data of company’s annual financial statement and annual report summary has been obtained from the official website of IDX. This type study is quantitative research. The sample used was companies manufacture in 2014-2018 totaling 26 samples. Data analysis method used in this study is regression analysis in panel data. The result of the study show that board of commissioner has a negative significant effect on value of the company (PBV). Institusional ownership has a significant negative  not effect on value of the company (PBV).Kata kunci : Independent board of commissioners, institutional ownership, firm value (PBV).